A comprehensive evaluation of anti-diabetic drugs on nuclear receptor PXR platform. (October 2019) - Singh, Shashi Kala; Yende, Ashutosh S.; Ponnusamy, Kalaiarasan; Tyagi, Rakesh K.
Abstract: Pregnane & Xenobiotic Receptor (PXR), one of the members of nuclear receptor superfamily, acts as a 'master-regulator' of drug metabolism and disposition machinery (DMD). Activation of PXR enables detoxification and elimination of toxic xenobiotics/endobiotics, and defends our body against chemical insults. On the contrary, PXR activation also imposes a serious concern for drug-drug interactions (DDIs). Such DDIs could either decrease the efficacy or lead to accumulation of co-administered drugs at toxic level. Therefore, it is desirable that during drug development process the small drug molecules are screened on PXR-platform prior to their clinical trial and prevent late stage failures. In view of this, we have selected a group of anti-diabetic drug molecules to examine if the success and potential failure of small molecule modulators can be pre-assessed and judiciously correlated on PXR platform. For this purpose, we have examined the PXR activation potential of the selected anti-diabetic drugs. Subsequent to screening of these anti-diabetic drugs, we elaborated the study further with rosiglitazone and pioglitazone (thiazolidinediones, TZDs) which are oral anti-diabetic formulations and have been in controversy owing to their association with cardiotoxicity and bladder cancer respectively. Our study revealed that some of the selected anti-diabetic drugs possess PXR activation potential, implying that these can up-regulate the expression of CYP3A4, UGT1A1, MDR1 and thereby can be predicted to inflict undesirable consequences. Highlights: Nuclear Receptor PXR-based assay may be used for the evaluation of small molecules. Modulatory effects of 10 anti-diabetic drugs were investigated on PXR level. Rosiglitazone and pioglitazone exhibited PXR-mediated activation of DMD machinery. Resources and time loss in developing a drug may be prevented by present protocol.